PTH-026 Roboscope – 2 centre initial experience. (June 2019) - Hearing, Stephen; Fletcher, Jonathan
Abstract : Introduction: Robotic colonoscopy was introduced to UK in 2015. It has previously been used in other European centres. Robotic colonoscopy is an automatic self-propelled, user guided, single use colonoscope which has been developed to enable successful caecal intubation, with reduced discomfort (painless colonoscopy). Methods: The technique has been piloted in a number of UK centres, results are presented for initial use in 2 centres. Results: Royal Derby Hospital 10 procedures undertaken: 1 was abandoned because of technical problems with the equipment. Of the 9 procedures undertaken, 4 were successful to the caecum, 5 were unsuccessful (3 to hepatic flexure, 2 to sigmoid). Of the 5 that were unsuccessful, all were changed to traditional colonoscopy and successful colonoscopy to the caecum was performed. Borders General Hospital 17 procedures undertaken: 9 were successful to the caecum, 8 were unsuccessful (4 to hepatic flexure, 4 to sigmoid). Of the 8 that were unsuccessful, all were changed to traditional colonoscopy and successful colonoscopy to the caecum was performed. Combined data Caecal Intubation rate 48% Mean Procedure time 74 minutes (23 patients) Analgesia requirements – 26 patients required opiate and midazolam, 1 patient Entonox only Conclusions: In the 2 centres trialling the Robotic colonoscopy, the technique is associated with low caecal intubation rate, long procedure times and analgesia requirements equivalent to traditional colonoscopy. Both units no longer carry out this procedure.